Making Sense of Refugees Online: Perspective Taking, Political Imagination, and Internet Memes. (April 2018) - Glăveanu, Vlad Petre; de Saint-Laurent, Constance; Literat, Ioana
There are many dimensions to the ongoing European refugee crisis, including economic, political, and humanitarian. Underlying them, however, is the issue of self–other relations and, in particular, the ways in which Western societies imagine others and otherness, defined in cultural, religious, and political terms. At the core of this political imagination, we propose, are certain understandings of refugees, of how they think, feel, and intend to act. In this article, we aim to unpack the social and psychological mechanisms involved in taking the perspective of refugees on digital platforms. The focus here is on refugee-related memes shared on Reddit, and the conversations around these visual artifacts. Our findings indicate that participants in these forums most often construct the perspective of refugees from an outside position, based on a commitment to difference, and rarely try to identify with the situation of refugees.